"We're not treated equally as Indigenous people or as women": The perspectives and experiences of Indigenous women in Australian public relations. (May 2021) - Clark, Treena; Dodson, Shannan; Guivarra, Nancia; Widders Hunt, Yatu
This paper argues that the public relations sphere needs to have better understanding and more representation and acknowledgment of Indigenous women's contemporary experiences and contributions. Indigenous Australian women experience multiple oppressions, such as Eurocentric and patriarchal control and, within the broader areas of Indigenous, women's, and feminist public relations scholarship, their voices are largely absent. To address these issues, this paper, based on Indigenous women's standpoint theory and an Indigenous yarning method, presents the narratives of five Aboriginal and Torres Strait Islander women employed in public relations. These narratives reflect experiences of marginalization by the Australian mainstream culture of whiteness and patriarchy; they also suggest the incidence of work induced mental distress for the women participants. This study of female Indigeneity within public relations aims to promote understanding of intersectional identities, the long-term effects of whiteness and racism, and may suggest how public relations can play a role in decolonizing efforts.